PENGARUH BUDIDAYA RUMPUT LAUT TERHADAP KUALITAS AIR LINGKUNGAN BUDIDAYA TAMBAK UDANG VANAME - Fitratul Muaddama; Damis Damis; Surianti Surianti; Hasrianti Hasrianti; Randi Randi (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
This study aims to determine the impact of seaweed cultivation on the water quality of vannamei shrimp aquaculture ponds in the Suppa District, Pinrang Regency. This research was conducted for approximately 10 (ten) years in 2020. The research location was around the waters of the Suppa District, Pinrang Regency. includes preparation / preliminary observation in the field, determining sample points or selecting observation stations, collecting data in the field, taking samples then observing the laboratory, and making reports. Analysis of water quality for seaweed cultivation includes parameters of Salinity, Temperature, DO, pH, Nitrate and Phosphate. Based on laboratory tests, it is known that for analysis of seaweed cultivation water quality, the average value of each parameter is temperature 30 0c, Salinity 36 ppt, DO 6.44 ppm, pH 8.30, Flow 0.35 m / s, Brightness 58%, Nitrate 0.005 mg / l, and 0.00026 ppm Phosphate While the results of laboratory analysis of physical and chemical parameters in the area of ​​vannamei shrimp pond cultivation in Suppa District, Pinrang Regency, it is known that the average value of each parameter is temperature 30 0c, Salinity 33 ppt, DO 6.0 ppm, pH 8.4, Nitrate 0.0061 mg / l, and Phosphate 0.0032 ppm. The analysis of the suitability of pond land based on the analysis carried out found that it was suitable for 727.66 ha. And the effect of seaweed cultivation is very good for its influence on the quality of white shrimp pond water.